Vacuum-free arc synthesis and characterization of crystalline molybdenum borides as instrumental material; Thermal Science and Engineering Progress; Vol. 67 - Vasiljeva (Vassilyeva) Yu. Z. Yuliya Zakharovna; Neklya Yu. A. Yuliya Aleksandrovna; Lukanov M. M. Mikhail Mikhailovich; Kvashnin A. G. Aleksandr Gennadjevich; Pak A. Ya. Aleksandr Yakovlevich (2025, 2025)
Title screen